Identification of Merkel cell polyomavirus in Merkel cell carcinoma tissue: case report of a Taiwanese patient - Wen-Tsao Ho; Jonathan Te Peng Tseng; Chung-Hong Hu; Wei-Hwa Lee; Tsung-Hsien Tsai (Wolters Kluwer Medknow Publications, 2010)
Merkel cell carcinoma (MCC) is a rare malignancy with aggressive behavior mostly seen in the elderly and immunosuppressed patients. In 2008, the clonal integration of a new human polyomavirus, named Merkel cell polyomavirus (MCPyV), was found to be closely associated with the development of MCC. This correlation was established by subsequent reports, mostly in Caucasians. To evaluate whether this correlation is also relevant among the Taiwanese population, we used polymerase chain reaction to detect the presence of MCPyV in a formalin-fixed and paraffin-embedded MCC specimen. In addition, we used tissue with seborrheic keratosis from the same patient as a control. Three different specific primer sets, LT1, LT3 and VP1, were used to amplify characteristic MCPyV genes, and large T antigen and VP1 genes, respectively. Amplicons of the expected sizes for all three primer pairs were detected in MCC tissue and amplicons for both LT3 and VP1 were detected in seborrheic keratosis tissue. More studies are needed to quantify viral positivity of MCPyV in various tissues of patients with MCC and to establish genetic interactions between the virus and host.